A New Model for Player Selection in Cricket. (1st April 2016) - Saikia, Hemanta; Bhattacharjee, Dibyojyoti; Radhakrishnan, Unni Krishnan
Abstract : A balanced squad in cricket contains players with different expertise like batting, bowling, all-rounder and wicket keeping. Maintaining these cricketing requirements, selecting an optimal squad is a difficult decision making problem. The selectors have chosen cricketers using their own experience and based on the recent performances of available players from all the different expertise. The paper introduces a measure that can quantify the performance of the cricketers into a single numerical value, which is a measure of the player's cricketing efficiency. The distributional pattern of the performance measure is identified and then used to recognize the performers under different expertise. The entire exercise simplifies the job of the selectors as they now have a smaller subset to choose from. To explain the model empirically, data of the Indian Premier League (IPL), 2012 is used to identify the performers of the game under different expertise. The actual Indian team selected just after the said season of IPL is then compared with the performers of IPL, 2012 as identified by the model. It was found that several non-performers were selected in the actual squad and some performers were left out. This model can be extended for the team selection in other versions of cricket and even in other team sports.